Laboratory performance evaluation of pristine and used headgear for girls` lacrosse - Kelshaw, P. M.; Gould, T. E.; Jesunathadas, M.; Cortes, N.; Caswell, A.; Edwards, E. D.; Caswell, S. V. (Journal of Applied Biomechanics, 2019)
Girls` lacrosse participation and head injury rates have increased within the past decade. In response, optional headgear was implemented following the recently developed ASTM International lacrosse headgear performance standards. It remains unknown how lacrosse headgear responds to blunt impacts after use. Our purpose was to compare the peak linear acceleration between girls` lacrosse headgear conditions (pristine and used) during blunt impacts. Pristine headgear (n=10) were tested in their original condition and used headgear (n=10) were worn for an entire competitive season. A Cadex Monorail Impactor impacted all headgear following ASTM standards (F1446-15b, F2220-15, and F3137-15) in the required testing locations. A 2×7 repeated-measures analysis of variance compared peak linear acceleration among headgear conditions and impact locations with a simple effects analysis planned comparison. There was no difference between headgear conditions for peak linear acceleration (pristine: 47.12 [13.92] g; used: 46.62 [14.84] g; F=2.11, P>.05). A main effect for impact location (F=983.52, P<.01), and an interaction effect of condition and impact location (F=12.79, P<.01) were observed. All headgear, regardless of condition, met the ASTM performance standard. This suggests that headgear performance may not degrade subsequent to a single season of high school girls` lacrosse.